Analysis of overcoming dormancy in Leucaena leucocephala seed and Initial development of plantlet - Mariano, Lilian Gonçalves; Somavilla, André; Silveira, Amanda Grassmann da; Salamoni, Adriana Tourinho (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2016)
Leucaena is an exotic fabaceae that has a much diversified utilization, highlighting the reforesting of degraded areas for the erosion control. For presenting a quite slow growth, the success of its cultivation is related to the sowing and seed emergency, that consequently require the utilization of methods of overcoming physic dormancy in seed germination to succeed. This paper aimed evaluates the effect of methods of overcoming dormancy on seed germination and on initial development of leucaena plantlet. The treatments used were: Witness (with no intervention); mechanic scarification with sandpaper number 100; immersion in H2SO4 (95 %) for 4 minutes and immersion in H2O at 80°C for 15 minutes. The mechanic scarification with sandpaper and water at 80ºC for 15 minutes presented the best results to percentage of germination. Although to index of speed emergency and plantlet height, the scarification was better.